2018
DOI: 10.1002/ar.23940
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: MiR‐141‐3p Suppresses Tumor Growth and Metastasis in Papillary Thyroid Cancer via Targeting Yin Yang 1

Abstract: has been found to be downregulated in papillary thyroid carcinoma (PTC), while little is known about the cellular functions and precise signals elicited by miR-141-3p in PTC. The results of this study indicated that the expression of miR-141-3p was aberrantly down-regulated in PTC tissues and cell lines, compared with the adjacent normal tissues and normal thyroid epithelial cells. Furthermore, the miR-141-3p expression level was negatively associated with TNM stage and lymph node metastasis in PTC. Expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 36 publications
(43 reference statements)
1
17
0
Order By: Relevance
“…However, little is known about the role of miR‐141‐3p in PTC. Our previous studies revealed that miR‐141‐3p alleviated PTC progression through negative regulating YinYang 1 expression (Fang et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, little is known about the role of miR‐141‐3p in PTC. Our previous studies revealed that miR‐141‐3p alleviated PTC progression through negative regulating YinYang 1 expression (Fang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al revealed that miR‐141‐3p functions as a tumor suppressor via downregulating ATF5 (Wang et al, ). More recently, our study revealed that miR‐141‐3p exerts inhibitory effects on cell proliferation and metastasis by downregulating Yin Yang 1(YY1) (Fang et al, ).…”
Section: Introductionmentioning
confidence: 95%
“…Although several studies have reported the downexpression of miR-200 family members in lung, 15 colon, 16 or breast tumors, 11 upregulation of miR-200 is upregulated in non-small-cell lung cancer 17 . Furthermore, enforced miR-200 expression promotes metastatic spread in breast cancer models,18, 19 but overexpression of miR-141 or miR-429 has been associated with a suppressor gene function in several tumor types 20, 21, 22, 23…”
Section: Introductionmentioning
confidence: 99%
“…miR-141-3p and miR-150 were separately demonstrated by different studies to be inversely associated with TNM stage and lymph node metastasis in PTC patients (53,58). Similarly, the inverse association between miR-199b-5p or miR-7 and TNM stage was shown in PTC patients (55,59).…”
Section: Ncrnas Playing Role As Prognostic Factors Of Thyroid Cancermentioning
confidence: 86%